2002
DOI: 10.1034/j.1600-0404.2002.1o143.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of electrical stimulation of lumbosacral roots in lumbar spinal stenosis

Abstract: Electrical root stimulation revealed more abnormalities in patients with LSS in comparison with needle EMG. However, both methods seemed to complement each other to show additional pathology in a given patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Study revealed distinct findings of both NCS and EMG and considered as it adds further diagnostic information [7]. This correlated to our study as both NC and EMG were equally important in diagnosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Study revealed distinct findings of both NCS and EMG and considered as it adds further diagnostic information [7]. This correlated to our study as both NC and EMG were equally important in diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…Regardless of abnormal MRI, electrodiagnostic abnormalities can help to select the best treatment option [6]. EDX can be utilized to separate neuromuscular problems, electromyography (EMG) method is utilized to restrict the myotomal conclusion and muscle examination is needed with both needle EMG and root stimulation [7]. The level of nerve damage is an important indicator in the clinical decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…For each nerve type, SEPs were obtained twice and the average of two latencies of the symptomatic side was compared with contralateral side. A latency delay of over 3 ms was defined as abnormal [ 11 12 13 ]. The electrodiagnostic study was performed using a certified machine (Medelec Synergy; Oxford Instruments, Surrey, UK).…”
Section: Methodsmentioning
confidence: 99%
“…In a small controlled trial with 20 persons with clinical spinal stenosis, EMG and nerve conduction findings detected 75% of cases while needle stimulation of the lumbar roots detected 85%. 43 Clinical Implications EDX has its strengths and weaknesses. In comparison with MRI, the equipment and testing are very cheap.…”
Section: Electrodiagnostic Findingsmentioning
confidence: 99%